2006
DOI: 10.1126/science.1126090
|View full text |Cite
|
Sign up to set email alerts
|

Drilling to Gabbro in Intact Ocean Crust

Abstract: Sampling an intact sequence of oceanic crust through lavas, dikes, and gabbros is necessary to advance the understanding of the formation and evolution of crust formed at mid-ocean ridges, but it has been an elusive goal of scientific ocean drilling for decades. Recent drilling in the eastern Pacific Ocean in Hole 1256D reached gabbro within seismic layer 2, 1157 meters into crust formed at a superfast spreading rate. The gabbros are the crystallized melt lenses that formed beneath a mid-ocean ridge. The depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
256
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 241 publications
(267 citation statements)
references
References 48 publications
11
256
0
Order By: Relevance
“…Two features seem particularly characteristic. The IODP and Oman RZSDC have a comparable $100 m thickness if, according to Wilson et al [2006], the top gabbros from the gabbro unit are represented by the last meters of the core. Most textures observed in the Hole 1256D also match those in Oman, as illustrated by the comparison of ophitic gabbros (Figures 15a and 15b; see also for Troodos ophiolite [Gillis and Coogan, 2002]).…”
Section: Rzsdc In Domains Affected By Ridge Segmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Two features seem particularly characteristic. The IODP and Oman RZSDC have a comparable $100 m thickness if, according to Wilson et al [2006], the top gabbros from the gabbro unit are represented by the last meters of the core. Most textures observed in the Hole 1256D also match those in Oman, as illustrated by the comparison of ophitic gabbros (Figures 15a and 15b; see also for Troodos ophiolite [Gillis and Coogan, 2002]).…”
Section: Rzsdc In Domains Affected By Ridge Segmentationmentioning
confidence: 99%
“…[47] On the basis of the observation of prograde mineral reactions in the granoblastic dikes, the ''granoblastic'' textures are ascribed by Teagle et al [2006] and Wilson et al [2006] to ''contact metamorphism by underlying gabbro intrusions.'' This agrees with the Troodos ophiolite study [Gillis and Roberts, 1999], where a large metamorphic aureole has been observed in sheeted dikes at the margins of a gabbronorite intrusion.…”
Section: Rzsdc In Domains Affected By Ridge Segmentationmentioning
confidence: 99%
“…[3] There are two methods of accessing subsurface ocean crust: deep crustal drilling [Alt et al, 1996;Wilson et al, 2006] and submersible investigations of tectonic escarpments, also known as ''tectonic windows'' [Karson, 2002;Karson et al, 2002aKarson et al, , 2002bPockalny et al, 2004]. The most recently investigated Pacific-crust tectonic window is the Pito Deep Rift (PDR), where in situ ocean crust generated at the SEPR is exposed along escarpments with kilometer-scale relief (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The base of the SDC is defined by the uppermost gabbroic intrusion at 1404.6 mbsf (Wilson et al, 2006). Recovery within the SDC was highly variable but averaged <12%.…”
Section: Downhole Distribution Of Chilled Marginsmentioning
confidence: 99%